2018
DOI: 10.1002/mp.13016
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric properties of colon polyps, cancer, and normal mucosa: Ex vivo measurements from 0.5 to 20 GHz

Abstract: The contrast in complex permittivities between normal and abnormal colon tissues presented here for the first time demonstrate the potential of these measurements for tissue classification. It also opens the door to the development of a microwave endoscopic device to complement the outcomes of colonoscopy with functional tissue information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
47
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 53 publications
(119 reference statements)
0
47
1
Order By: Relevance
“…Biological tissues feature inherent dielectric properties, which are often expressed in terms of permittivity and conductivity, based on the interaction of an external field with the electric dipole moment of the samples [Volkov and Prokhorov, ]. Over the last few decades, the open‐ended coaxial probe method [Athey et al, ; Bobowski and Johnson, ] has been explored as a means to measure the dielectric properties of the tissues [Gabriel et al, ; Li et al, , ; Guardiola et al, ; Mirbeik et al, ]. The results indicated that the dielectric properties of human cancer tissues and the corresponding normal tissues are often quite different.…”
Section: Introductionmentioning
confidence: 99%
“…Biological tissues feature inherent dielectric properties, which are often expressed in terms of permittivity and conductivity, based on the interaction of an external field with the electric dipole moment of the samples [Volkov and Prokhorov, ]. Over the last few decades, the open‐ended coaxial probe method [Athey et al, ; Bobowski and Johnson, ] has been explored as a means to measure the dielectric properties of the tissues [Gabriel et al, ; Li et al, , ; Guardiola et al, ; Mirbeik et al, ]. The results indicated that the dielectric properties of human cancer tissues and the corresponding normal tissues are often quite different.…”
Section: Introductionmentioning
confidence: 99%
“…1. This design is widely used in [16] Not available yet a ADR (Adenoma Detection Rate) is most important indicator of quality in colonoscopy and measures the proportion of colonoscopies in which at least one adenoma is found. This increase is referenced to conventional colonoscopy.…”
Section: System Requirements and Challengesmentioning
confidence: 99%
“…Robustness is one of the main requirements for using a MI system in a clinical environment that is especially rich in electromagnetic interferences and noise, which can lead to errors in the measured data. For this application, the frequency range 5-8 GHz gives the highest contrast among healthy colon, different types of polyps and cancer [15,16]. Furthermore, realtime, computationally-efficient and accurate imaging algorithms are required.…”
Section: System Requirements and Challengesmentioning
confidence: 99%
See 2 more Smart Citations